TINJAUAN YURIDIS PERLINDUNGAN HUKUM BAGI PARA PIHAK DALAM PERWAKILAN SUKARELA (ZAAKWAARNEMING) YANG MENYEBABKAN KERUGIAN - M. Fajrin Putra (Fakultas Hukum Universitas Islam Malang, 2021)
ABSTRACTAware of his duty as a provider of legal protection for every citizen as a form of enforcement of the mandate of the rule of law as stated in Article 1 paragraph (3) of the 1945 Constitution, the state must in essence always be present to facilitate the interaction of every human being as an orderly, safe, comfortable, and comfortable citizen. because actually citizens are human beings in relation to social beings. A legal relationship between humans or individuals with one another is called an engagement. The engagement as referred to can be sourced from the law. One form of engagement that was born because of the law is voluntary representation (zaakwarneming). A person who has volunteered is also required to do all the obligations that must be done, it is the responsibility of the party who has represented. In practice, the act of voluntary representation (zaakwaarneming) always has the potential for errors to occur which can lead to losses. This is because the competence of a person acting as a voluntary representative cannot be ascertained to have the ability commensurate with the affairs being represented.Keywords: Legal Protection, Voluntary Representation, Loss ABSTRAKSadar akan tugasnya sebagai pemberi perlindungan hukum bagi setiap warga negaranya sebagai bentuk penegakan amanat negara hukum sebagaimana tertuang dalam Pasal 1 ayat (3) UUD 1945, negara pada hakikatnya harus selalu hadir untuk mempermudah interaksi setiap manusia sebagai warga negara yang tertib, aman, nyaman, karena sejatinya warga negara merupakan manusia dalam kaitannya dengan makhluk sosial. Suatu hubungan hukum antara manusia atau individu yang satu dengan yang lainnya dinamakan dengan perikatan. Perikatan sebagaimana yang dimaksud dapat bersumber dari undang-undang. Salah satu bentuk perikatan yang lahir karena undang-undang merupakan perwakilan sukarela (zaakwarneming). Seseorang yang telah melakukan sukarela diwajibkan pula mengerjakan segala kewajiban yang harus dikerjakan, sudah menjadi tanggung jawab bagi pihak yang telah mewakili. Dalam pelaksanaannya, perbuatan perwakilan sukarela (zaakwaarneming) selalu memiliki potensi akan terjadinya kesalahan yang berujung pada timbulnya kerugian. Hal ini dikarenakan kompetensi seseorang yang bertindak sebagai wakil sukarela tidak dapat dipastikan memiliki kemampuan yang sepadan dengan urusan yang diwakilkan.Kata Kunci: Perlindungan Hukum, Perwakilan Sukarela, Kerugian